ChemInform Abstract: A Robust, Eco‐Friendly Access to Secondary Thioamides Through the Addition of Organolithium Reagents to Isothiocyanates in Cyclopentyl Methyl Ether (CPME). Issue 19 (April 2016) - Pace, Vittorio; Castoldi, Laura; Monticelli, Serena; Safranek, Sandra; Roller, Alexander; Langer, Thierry; Holzer, Wolfgang
Abstract: The nucleophilic addition of organolithium reagents to isothiocyanates affords secondary thioamides in a straightforward, high‐yielding, one‐pot method.